The Role of Regional Monitoring Assembly (MPD) Taking Control of The Check / Honorarium Services in The District of Cirebon - Arif Rakhman; Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Notary as a public official, as well as a profession, position is very important in helping to provide legal certainty for the public. Notaries must prevent legal problems later in life through authentic agreement he made as a perfect proof in court. Notaries have a role in activities run the legal profession that can not disconnect from the fundamental issues relating to the functions and roles of law where the law itself, which is defined as the legal rules that govern all public life. This authority can not be applied because it has not yet issued the implementing regulations for the expansion of the notary's authority.Keywords: Notary Official; The Function of Notaries; Notary Competition.